The Representation of Javanese People in the Film "De Oost" by Jim Taihuttu: A Semiotic Analysis by Roland Barthes - Arya, Aurel Evan; Sokowati, Muria Endah (Jurnal Audiens, 2024)
Jim Taihuttu's film "De Oost" explores the Dutch colonial period in Indonesia and has drawn attention from researchers interested in how Javanese people are portrayed in cinema. The study employs Roland Barthes' semiotic analysis to analyze the film's representations, revealing that Javanese characters are frequently depicted in stereotypical and subordinate roles that are influenced by Western perspectives. This analysis examines both the apparent and deeper meanings of the representations. Although certain sequences endeavor to demonstrate the complexity and agency of Javanese characters, these representations continue to primarily perpetuate preexisting stereotypes, underscoring the necessity of more precise and equitable media representations. In the film "De Oost," Javanese characters are predominantly depicted in a manner that aligns with the Orientalist perspective, which implies that they are frequently portrayed as stereotypical and of lesser significance. The majority of Javanese characters are depicted in stories that are dominated by Western perspectives, despite the fact that certain sequences attempt to demonstrate their depth and strength. This means that even though there are moments of resistance, the overall portrayal doesn't significantly challenge the dominant narrative.